STUDI KOMPARATIF ANTUSIASME SISWA TERHADAP MEDIA ANGKLUNG PADA PEMBELAJARAN IPAS KELAS IV - Shofyana, Nadia; Dea Rahma Putri; Marliana Putri Lestari; Wasis Wijayanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Angklung is a traditional West Javanese musical instrument that can be used as a learning medium, especially in local wisdom material in science subjects in elementary schools. The use of angklung media shows variations in student enthusiasm as reflected in responses, attention, and participation. This condition indicates the need for a study comparing student enthusiasm towards the use of angklung media in different schools. This study aims to compare student enthusiasm towards the use of angklung media in science learning on local wisdom material in two elementary schools. This study uses a quantitative approach with a comparative design. The subjects of the study were fourth-grade students at SD N 1 Bae and SD N 3 Bae, each numbering 15 students, resulting in a total of 30 students. Data were collected through observation, questionnaires, and documentation, then analyzed using statistical tests on IBM SPSS. The results of the analysis showed a significance value (2-tailed) of 0.179 (>0.05), so that H₀ which states there is no difference in student enthusiasm between SD N 1 Bae and SD N 3 Bae is accepted. The t-value of -1.379 also indicates a relatively small difference in student enthusiasm. Thus, it can be concluded that fourth-grade students at SD N 1 Bae and SD N 3 Bae have the same level of enthusiasm for the use of angklung media in science learning on local wisdom.